Analysis and design of plasma monopole antenna - Wei, Li; Jinghui, Qiu; Ying, Suo (Видавництво Національного університету "Львівська політехніка", 2009)
Two kinds of plasma monopole antennas are simulated and analyzed in this paper. For different radius, reflection coefficient, radiation pattern and radiation efficiency of a cylindrical plasma monopole antenna are calculated respectively. According to actual situation, a conical plasma monopole antenna with different cone angle is simulated. Impedance and radiation characteristics of the plasma antenna are similar to the metal monopole antenna.
Keywords: pasma antenna; monopole antenna; radiation characteristics